Adaptability and stability of wheat genotypes according to the phenotypic index of seed vigor - Szareski, Vinícius Jardel; Carvalho, Ivan Ricardo; Kehl, Kassiana; Levien, Alexandre Moscarelli; Nardino, Maicon; Dellagostin, Simone Morgan; Demari, Gustavo Henrique; Lautenchleger, Francine; Villela, Francisco Amaral; Pedó, Tiago; et al. (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the adaptability and multi-trait stability of wheat (Triticum aestivum) genotypes according to the phenotypic index of seed vigor (PIV). Thirty wheat genotypes were grown in seven environments in the state of Rio Grande do Sul, Brazil, during one crop season. In each environment, a randomized complete block design with three replicates was used. The PIV was elaborated from the following traits: first germination count, germination percentage, accelerated aging, and electrical conductivity. The evaluated phenotypic index makes it possible to define macroenvironments for the production of wheat seeds with high physiological potential and to understand the implications of the genotype x environment interaction. The phenotypic index of seed vigor is effective to rank genotypes considering multi-trait selection related to the vigor of wheat seeds produced in Southern Brazil.